Cowaxanthone F, a new tetraoxygenated xanthone, and other anti-inflammatory and antioxidant compounds from Garcinia cowa - Panthong K. (2014)
A new tetraoxygenated xanthone, cowaxanthone F (1), as well as four known compounds, morelloflavone (2), volkensiflavone (3), morelloflavone-7"-0- glucoside (fukugiside, 4), and 1,6-dihydroxyxanthone (5), were isolated from the crude acetone extract of the twigs of Garcinia cowa (Guttiferae). All compounds (1-5) were tested for antioxidant activity against DPPH (diphenylpicrylhydrazyl), hydroxyl, and superoxide radicals; only morelloflavone (2) and morelloflavone-7"- O-glucoside (4) exhibited high potency. Eight tetraoxygenated xanthones from the fruits of G. cowa, cowaxanthones A-D (6-9), cowanin (15), a-mangostin (16), mangostanin (17), and cowanol (18), were also investigated for anti-inflammatory activity using ethyl phenylpropiolate (EPP)-induced ear edema. Assessment at 30, 60, and 120 min revealed that cowaxanthones B-D (7-9), cowanin (15), and a-mangostin (16) exhibited significant anti-inflammatory activity when compared to phenylbutazone, while cowaxanthone A (6), mangostanin (17), and cowanol (18) showed less activity.